How to Continue a Meaningful Judicial Dialogue About EU Law? From the Conditions in the CILFIT Judgment to the Creation of a New European Legal Culture - van Dorp, Jacobien; Phoa, Pauline (Utrecht Journal of International and European Law, 2018)
The aim of this article is to better understand the conditions outlined in the CILFIT judgment and their role in creating a meaningful dialogue about European Union law. For these purposes two distinct views on the relation between language and meaning are utilised, as has been argued for by Ludwig Wittgenstein in his Philosophical Investigations. In the CILFIT judgment both of these views surface, which imply different challenges to the participants of the EU dialogue. In the conclusion, we suggest how these challenges can be met in order to facilitate a mutually meaningful dialogue about EU law.